Bereitstellung von Umweltdaten im Baubereich auf der Grundlage statistischer Zusammenhänge zwischen den Wirkungsindikatoren einer - Ströbele, Benjamin (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft / Hrsg.: Karlsruher Institut für Technologie, Lehrstuhl, 2017)
Consideration of environmental data for comparison of building variants and building products strongly relies on a suitable provision of the respective data. The various environmental issues create a large variety of different data and parameters. In this study, two approaches are developed to remedy the related problem of multi-criterion decision-making. Whereas the first approach comprises finding proxy indicators, the second deals with the aggregation of the indicators on environmental impact indices.